2014
DOI: 10.1039/c4nr03340j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped one-dimensional (1D) macroporous carbonaceous nanotube arrays and their application in electrocatalytic oxygen reduction reactions

Abstract: A nitrogen(N)-doped one-dimensional (1D) macroporous carbonaceous nanotube array was fabricated by using an anodic alumina oxide (AAO) template. The large diameter of the nanotubes (∼200 nm) could overcome the sluggish mass transfer phenomena in the common micro/mesoporous carbon-based electrodes. Combining the activation of the π electrons of the sp(2) carbon array by N-doping, the novel 1D macroporous carbonaceous nanotube array exhibited high performance for the oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…3b), the high-resolution C 1s core-level spectrum could be deconvoluted into three peaks centered at $284.9, $285.9, and $289.2 eV, which was indexed to C]C/C-C, C-OH and C-O-Ni, respectively. [36][37][38] The sharpest peak corresponding to C]C/C-C indicated that most of the carbon atoms were in the form of a conjugated honeycomb lattice. The O 1s spectrum is deconvoluted into two peaks (Fig.…”
Section: -7mentioning
confidence: 99%
“…3b), the high-resolution C 1s core-level spectrum could be deconvoluted into three peaks centered at $284.9, $285.9, and $289.2 eV, which was indexed to C]C/C-C, C-OH and C-O-Ni, respectively. [36][37][38] The sharpest peak corresponding to C]C/C-C indicated that most of the carbon atoms were in the form of a conjugated honeycomb lattice. The O 1s spectrum is deconvoluted into two peaks (Fig.…”
Section: -7mentioning
confidence: 99%
“…For instance, recently, by using a co-pyrolysis route of Fe-Phthalocyanine loaded and PEO20-PPO70-PEO20 (P123) retained in mesoporous silica, Wang et al [34] synthesized NCNTs with well-defined morphology and graphitic structure, which exhibited good performance for ORR. Based on CVD, She et al fabricated N-doped 1D macroporous carbonaceous nanotube arrays in anodic alumina oxide (AAO) template, which also showed high performance for ORR [27]. In addition to the precursors and pyrolysis temperatures, for each method, other factors, such as time, gas flow rate, catalysts, also have significant influence on the nitrogen contents and the accurately controlled doping sites [17,28,39,40].…”
Section: In Situ Dopingmentioning
confidence: 99%
“…The typical in situ doping techniques include high-temperature arc-discharge [21,22], chemical vapor deposition (CVD) [23][24][25][26][27], chemically solvothermal procedures (ca. 230-300 °C), [28] and laser ablation methods [29,30].…”
Section: In Situ Dopingmentioning
confidence: 99%
“…According to theoretical calculation and experimental observation, an appropriate porous structure with large surface area is available to improve the ORR activity of N-doped carbon materials [1,2,[11][12][13]. Therefore, many strategies have been contributed to increasing the porosity and surface area of NNMCs by means of high specific surface area carbon materials (e.g., mesoporous carbon, graphene, carbon nanotube) [5,6,10], sacrificial inorganic hard templates (including ordered mesoporous silica, nano silicon, nano metal oxides) [2,[12][13][14][15], high specific surface area precursor materials (especially for the series of metal-organic frameworks, e.g., MOFs: MOF-5, Al-PCP, ZIF-8) [11,[16][17][18][19], and other miscellaneous techniques [2,5]. In spite of many advantages, such traditional synthesis routes for the porous carbon material typically involve multi-step procedures including syntheses of various hard templates, followed by the immersion of N-carbon precursors and the carbonization at high temperature, and then the removal of the inorganic matrix via strong alkali or acidic.…”
Section: Introductionmentioning
confidence: 99%